Intrathecal administration of AAV/GALC vectors in 10–11‐day‐old twitcher mice improves survival and is enhanced by bone marrow transplant. Issue 11 (November 2016) - Karumuthil‐Melethil, Subha; Marshall, Michael S.; Heindel, Clifford; Jakubauskas, Benas; Bongarzone, Ernesto R.; Gray, Steven J.
Abstract : Globoid cell leukodystrophy (GLD), or Krabbe disease, is an autosomal recessive neurodegenerative disease caused by the deficiency of the lysosomal enzyme galactocerebrosidase (GALC). Hematopoietic stem cell transplantation (HSCT) provides modest benefit in presymptomatic patients but is well short of a cure. Gene transfer experiments using viral vectors have shown some success in extending the survival in the mouse model of GLD, twitcher mice. The present study compares three single‐stranded (ss) AAV serotypes, two natural and one engineered (with oligodendrocyte tropism), and a self‐complementary (sc) AAV vector, all packaged with a codon‐optimized murine GALC gene. The vectors were delivered via a lumbar intrathecal route for global CNS distribution on PND10–11 at a dose of 2 × 10 11 vector genomes (vg) per mouse. The results showed a similar significant extension of life span of the twitcher mice for all three serotypes (AAV9, AAVrh10, and AAV‐Olig001) as well as the scAAV9 vector, compared to control cohorts. The rAAV gene transfer facilitated GALC biodistribution and detectable enzymatic activity throughout the CNS as well as in sciatic nerve and liver. When combined with BMT from syngeneic wild‐type mice, there was significant improvement in survival for ssAAV9. Histopathological analysis of brain, spinal cord, and sciatic nerve showed significant improvement in preservation of myelin, with ssAAV9 providing the greatest benefit. In summary, we demonstrate that lumbar intrathecal delivery of rAAV/mGALCopt can significantly enhance the life span of twitcher mice treated at PND10–11 and that BMT synergizes with this treatment to improve the survival further. © 2016 Wiley Periodicals, Inc. Abstract : Intrathecal AAV‐mediated gene therapy synergized with bone marrow transplant (BMT) in the 10–11‐day‐old twitcher mouse model of Krabbe disease to extend the survival as well as to improve the pathology in the CNS and sciatic nerve.